An assessment of a health education program addressing overweight, obesity and lifestyle modification in Ghana - Jane Barnes; Sandra Boatemaa Kushitor; Millicent Ofori Boateng; Edward Kofi Sutherland; James Avoka; Stephen Manortey (PLoS ONE, 2025)
Background Obesity is a significant risk factor for several comorbidities, including type II diabetes, cancer, and cardiovascular diseases. Recent studies suggest an increase in the prevalence of overweight and obesity among rural residents. Yet interventions to create awareness and promote lifestyle modifications are limited in rural areas. Aim The aim of this paper is to assess the effect of a nutrition education intervention in enhancing overweight and obesity knowledge and lifestyle modification in a rural area in the Eastern Region of Ghana. Methods The study employed an exploratory sequential mixed-methods design and implemented a community-based intervention that involved nutrition education sessions, including songs, food demonstrations, and community engagement called the Oklebenor Awareness Program. Baseline and end-line surveys and in-depth interviews were conducted on the socio-demographic characteristics, participants’ knowledge, attitudes, and behaviours regarding overweight and obesity. The quantitative data were analysed using means, frequencies and T-test. The in-depth interviews were analysed using thematic analysis (n = 22). Results The average attendance during the lessons was 45 participants. About 50% of the respondents attended 4 lessons. The participants reported the Oklebenor Awareness Program as their main source of knowledge on overweight and obesity (n = 21). The mean score on the Obesity Risk Knowledge Score-10 increased from 5.3 at baseline to 6.6 at endline (mean change = 1.39, p = 0.001). Risk factors of overweight and obesity reported by the participants included unhealthy eating, physical inactivity, alcohol consumption and intentional weight gain. Lifestyle changes reported by the participants due to the intervention included increased dietary diversity by including legumes, fruits and vegetables in their meals and physical activity. Conclusion The nutrition education intervention enhanced participants’ knowledge of overweight and obesity and promoted dietary diversity and physical activity. Incorporating culturally sensitive approaches and involving families and community resources contributed to the success of the intervention. The findings highlight the need for health education programs to address the rising prevalence of overweight and obesity in rural areas.